Prostaglandin E2 promotes hepatic bile acid synthesis by an E prostanoid receptor 3‐mediated hepatocyte nuclear receptor 4α/cholesterol 7α‐hydroxylase pathway in mice. Issue 3 (31st December 2016) - Yan, Shuai; Tang, Juan; Zhang, Yuyao; Wang, Yuanyang; Zuo, Shengkai; Shen, Yujun; Zhang, Qianqian; Chen, Di; Yu, Yu; Wang, Kai; Duan, Sheng‐Zhong; Yu, Ying
Abstract : Prostaglandin E2 (PGE2 ) is an important lipid mediator of inflammation. However, whether and how PGE2 regulates hepatic cholesterol metabolism remains unknown. We found that expression of the PGE2 receptor, E prostanoid receptor 3 (EP3) expression is remarkably increased in hepatocytes in response to hyperlipidemic stress. Hepatocyte‐specific deletion of EP3 receptor ( EP3 hep–/– ) results in hypercholesterolemia and augments diet‐induced atherosclerosis in low‐density lipoprotein receptor knockout ( Ldlr –/– ) mice. Cholesterol 7α‐hydroxylase (CYP7A1) is down‐regulated in livers of EP3 hep–/– Ldlr −/− mice, leading to suppressed hepatic bile acid (BA) biosynthesis. Mechanistically, hepatic‐EP3 deficiency suppresses CYP7A1 expression by elevating protein kinase A (PKA)‐dependent Ser143 phosphorylation of hepatocyte nuclear receptor 4α (HNF4α). Disruption of the PKA‐HNF4α interaction and BA sequestration rescue impaired BA excretion and ameliorated atherosclerosis in EP3 hep–/– Ldlr −/− mice. Conclusion : Our results demonstrated an unexpected role of proinflammatory mediator PGE2 in improving hepatic cholesterol metabolism through activation of the EP3‐mediated PKA/HNF4α/CYP7A1 pathway, indicating that inhibition of this pathway may be a novel therapeutic strategy for dyslipidemia and atherosclerosis. (Hepatology 2017;65:999‐1014)